2017
DOI: 10.1186/s12984-017-0236-z
|View full text |Cite
|
Sign up to set email alerts
|

Overground vs. treadmill-based robotic gait training to improve seated balance in people with motor-complete spinal cord injury: a case report

Abstract: BackgroundRobotic overground gait training devices, such as the Ekso, require users to actively participate in triggering steps through weight-shifting movements. It remains unknown how much the trunk muscles are activated during these movements, and if it is possible to transfer training effects to seated balance control. This study was conducted to compare the activity of postural control muscles of the trunk during overground (Ekso) vs. treadmill-based (Lokomat) robotic gait training, and evaluate changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 28 publications
(38 reference statements)
3
46
1
Order By: Relevance
“…However, these neurological examinations rely only on sensory testing to infer the level of motor function in the trunk, and so any motor sparing of the trunk muscles may be missed. Indeed, recent evidence has shown that many individuals who have been classified with a high‐thoracic or cervical mcSCI retain sparing of trunk muscles, thus presenting the opportunity to develop new interventions to recruit and strengthen the trunk muscles to improve functional seated balance in this population . Our results suggest that our ACE “spin” training program may be an effective way to actively target and train trunk muscles, even for those with high‐thoracic/cervical injuries who may have difficulty performing traditional trunk exercises.…”
Section: Discussionmentioning
confidence: 81%
“…However, these neurological examinations rely only on sensory testing to infer the level of motor function in the trunk, and so any motor sparing of the trunk muscles may be missed. Indeed, recent evidence has shown that many individuals who have been classified with a high‐thoracic or cervical mcSCI retain sparing of trunk muscles, thus presenting the opportunity to develop new interventions to recruit and strengthen the trunk muscles to improve functional seated balance in this population . Our results suggest that our ACE “spin” training program may be an effective way to actively target and train trunk muscles, even for those with high‐thoracic/cervical injuries who may have difficulty performing traditional trunk exercises.…”
Section: Discussionmentioning
confidence: 81%
“…We identified 1,081 unique records through database searching and one addition through reference searching ( Figure 1 ). Of those, 139 records remained after title and abstract screening, of which 50 met the inclusion criteria and were analyzed (Husemann et al, 2007 ; Mayr et al, 2007 ; Freivogel et al, 2008 , 2009 ; Lo and Triche, 2008 ; Ng et al, 2008 ; Hesse and Werner, 2009 ; Borggraefe et al, 2010 ; Chin et al, 2010 ; Lo et al, 2010 ; Geroin et al, 2011 ; Morone et al, 2011 ; Turiel et al, 2011 ; Benito-Penalva et al, 2012 ; Carda et al, 2012 ; Gizzi et al, 2012 ; Picelli et al, 2012 , 2015 ; Vaney et al, 2012 ; Geigle et al, 2013 ; Kelley et al, 2013a , b ; Aach et al, 2014 ; Labruyère and van Hedel, 2014 ; Nilsson et al, 2014 ; Stoller et al, 2014 , 2015 ; Asbeck et al, 2015 ; Filippo et al, 2015 ; Ochi et al, 2015 ; Schoenrath et al, 2015a , b ; Sczesny-Kaiser et al, 2015 , 2017 ; Wu et al, 2015 ; Chua et al, 2016 ; Forrester et al, 2016 ; Ikumi et al, 2016 ; Kumru et al, 2016a , b ; Aurich-Schuler et al, 2017 ; Bae et al, 2017 ; Chisholm et al, 2017 ; Esquenazi et al, 2017 ; Grasmücke et al, 2017 ; Jansen et al, 2017 , 2018 ; Kim et al, 2019 ; Straudi et al, 2019 ; Tanaka et al, 2019 ). We identified some studies with overlap in patients (Kelley et al, 2013a , b ; Aach et al, 2014 ; Stoller et al,…”
Section: Resultsmentioning
confidence: 99%
“…The intense training of the impaired limb and the acquisition of new motor skills mediate functional recovery through the sprouting of new synapses [ 5 ]. Enhancement of trunk muscle activity during robot training may lead to improvement in balance control [ 21 ]. Improved balance control from standing to sitting shows an improved gait function.…”
Section: Discussionmentioning
confidence: 99%